2012
DOI: 10.12938/bmfh.31.47
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lacto-<i>N</i>-biose I on the Antigen-specific Immune Responses of Splenocytes

Abstract: We examined the effect of lacto-N-biose I (LNB) on Antigen (Ag)-specific responses of immune cells. LNB exposure in vitro suppressed Ag-specific Interleukin (IL)-4 secretion of mouse splenocytes significantly. However, IL-4 secretion from CD4+ T cells stimulated with anti-CD3ε did not changed significantly with LNB exposure. Additionally, Ag-specific Th1 cytokines did not change. Therefore LNB might suppress Ag-specific IL-4 through modification of Ag-presenting cells (APCs) in a manner independent of Th1-type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…on the previous research, the LNB immunomodulatory behavior employing mice's naive immune cell expressing Receptor T-cells (TCR) especially chicken ovalbumin (OVA) demonstrated that the LNB exposure greatly decreased the Ag-specific production of IL-4 [33]. IL-4 is the leading development of the ag-specific Th2 cell in association with cytokine.…”
Section: Basedmentioning
confidence: 95%
See 1 more Smart Citation
“…on the previous research, the LNB immunomodulatory behavior employing mice's naive immune cell expressing Receptor T-cells (TCR) especially chicken ovalbumin (OVA) demonstrated that the LNB exposure greatly decreased the Ag-specific production of IL-4 [33]. IL-4 is the leading development of the ag-specific Th2 cell in association with cytokine.…”
Section: Basedmentioning
confidence: 95%
“…It changes the effect of Gal-3, which binds LNB to damage the function partially and only reduce the secretion of Ag-specific IL-4. In general, by the modification of APCs signal, LNB affects Ag-specific immune response [33].…”
Section: Basedmentioning
confidence: 99%